Biocomputing 2015 2014
DOI: 10.1142/9789814644730_0006
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genome-Wide Analysis of the Determinants of Rna Splicing in Kidney Renal Clear Cell Carcinoma

Abstract: We present a genome-wide analysis of splicing patterns of 282 kidney renal clear cell carcinoma patients in which we integrate data from whole-exome sequencing of tumor and normal samples, RNA-seq and copy number variation. We proposed a scoring mechanism to compare splicing patterns in tumor samples to normal samples in order to rank and detect tumor-specific isoforms that have a potential for new biomarkers. We identified a subset of genes that show introns only observable in tumor but not in normal samples,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, the full TuPro cohort represents a valuable resource to explore the use of Level 3 data in order to identify putative novel biomarker predictors in cancer (e.g., marker expression, activated pathways, sample composition). Additionally, association studies of data across modalities and detailed analyses of DNA, RNA, protein, and pathway aberrations in cancer will likely lead to a better and more comprehensive understanding of the TuPro tumors’ biology (Lehmann et al 2015; PCAWG Transcriptome Core Group et al 2018; Kahles et al 2018). These analyses can then support clinical trials on these Level 3 data biomarkers for their establishment as Level 1 or 2 data, closing the loop from exploratory science to clinical practice ( Figure 1A ).…”
Section: Exploratory and Integrative Analysesmentioning
confidence: 99%
“…Furthermore, the full TuPro cohort represents a valuable resource to explore the use of Level 3 data in order to identify putative novel biomarker predictors in cancer (e.g., marker expression, activated pathways, sample composition). Additionally, association studies of data across modalities and detailed analyses of DNA, RNA, protein, and pathway aberrations in cancer will likely lead to a better and more comprehensive understanding of the TuPro tumors’ biology (Lehmann et al 2015; PCAWG Transcriptome Core Group et al 2018; Kahles et al 2018). These analyses can then support clinical trials on these Level 3 data biomarkers for their establishment as Level 1 or 2 data, closing the loop from exploratory science to clinical practice ( Figure 1A ).…”
Section: Exploratory and Integrative Analysesmentioning
confidence: 99%
“…Recent studies have demonstrated the role of abnormal AS in KIRC (Lehmann et al, 2015;Li et al, 2017a (Li et al, 2017b). Differential expression of LENG8 in breast cancer has been confirmed (Ye et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have demonstrated the role of abnormal AS in KIRC (Lehmann et al, ; Li et al, ). However, there have been no reports of a comprehensive assessment of the prognostic power of AS events in KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated splicing occurs in carcinomas, resulting in various products with function and nonfunction. The events from cancer-specific splicing easily promote the development of disease [ 32 ]. Abnormal splicing exerts an effect on many carcinomas and brought about multiple features.…”
Section: Discussionmentioning
confidence: 99%